(untitled) (Proceeding of the International Conference on Arts and Humanities, 2021)
In creating a musical composition, a music composer often depends on anomalous skills and abilities such as recalling the timbre of a specific musical instrument, reading into an entirely unique language different from any spoken language in the world, and imagining inanimate objects as sound-emitting entities. Because of the possible interactions among these challenging and complex skills and ideas, it is thus important for the composer to have a plan in structuring the composition or a pre-compositional overview before going into the actual creative process of producing a coherent, meaningful piece. The structure or organization assists the composer in examining the interaction of the micro elements within the macro of the composition. It determines the final form of the composition as perceived by the composer. In this article, the structuring of Taming Sari, a composition for Trumpet, Oboe and String Quintet, is traced through an analysis of the composition process. The emphasis is on the complementary roles of both the technical and non-technical elements in producing and projecting a lived experience of the composition.